Hak Kepemilikan Mahar Berupa Tanah dalam Hukum Perkawinan (Analis Menurut Undang-Undang Pokok-Pokok Agraria) - Supriadi Supriadi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2019)
AbstractUU No. 1 of 1974 concerning marriage and Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Law (KHI) is one form of unification and codification of the law in Indonesia concerning marriages governing legal consequences including dowry in the form of land. Land law in Indonesia has been based on UU. No. 5 of 1960 concerning Basic Principles of Agrarian Law (UUPA) and Government Regulation No. 24 of 1997 concerning land registration. The issue of dowry in the form of land in the marriage law is inseparable from the provisions of agrarian law. In the principles view of the establishment of